Molecular cloning of microdissected lampbrush loop DNA sequences of Drosophila hydei - Hennig, Wolfgang (1983)
We microdissected a Y chromosomal lampbrush loop pair from primary spermatocyte nuclei of Drosophila hydei and cloned the DNA directly at the microscale. Four of the 12 recombinant DNA clones recovered display in situ hybridization to mitotic metaphase Y chromosomes, preferentially in the chromosomal region identified as the origin of the lampbrush loop pair. All clones, however, also hybridize to autosomal and X chromosomal loci in polytene chromosomes. Y chromosomal DNA sequences of D. hydei again prove to be members of different families of repeated sequences distributed throughout the genome. These microcloning experiments, which were carried out under very unfavourable experimental conditions (low DNA content of the lampbrush loops in the presence of large amounts of RNA) prove that almost any chromosomal structure detected by light microscopy is directly accessible to molecular cloning experiments by micromethods.